Challenges of Personnel Management in Local Government: A Case Study of Phonethong District, Luang Prabang Province, Lao PDR - Soulithai, khampouis; Keoboualaphet, Soulideth; Sisombath, Sithonh (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
This study aims tocontribute to the discourse on decentralization and civil service reform in developing contexts. As governments pursue decentralization and administrative reform, effective human resource management at the district level becomes increasingly critical. However, few studies have examined human resource management at the district level. Rural districts such as Phonethong continue to face systemic challenges that undermine institutional efficiency, staff motivation, and the quality of public service delivery. Using a mixed-methods approach, this study collected data from 50 civil servants through structured questionnaires and conducted semi-structured interviews with 10 key informants, including administrative leaders and human resource officers. The results reveal five major areas of concern: (1) inadequate access to relevant and regular training programs; (2) ineffective and often symbolic performance evaluations; (3) low staff motivation, driven by unclear promotion pathways and poor working conditions; (4) limited digital skills and infrastructure; and (5) institutional rigidity and cultural barriers in managing diverse communities. The findings suggest that, although national policies aim to promote decentralized governance and strengthen human resource capacity, implementation at the district level remains weak and fragmented. Staff development is hindered by limited resources, favoritism in training allocation, and a lack of strategic planning. Furthermore, digital transformation efforts are minimal, and civil servants continue to rely on outdated administrative processes. The study concludes that addressing these human resource management challenges requires a multi-faceted strategy involving policy alignment, localized capacity-building, transparent performance evaluation systems, and greater administrative autonomy for district authorities. This research offers practical insights for policymakers, administrators, and development partners seeking to improve human resource systems in local governments across Laos. It also contributes to the broader discourse on public sector reform and decentralization in developing countries.